HISTOIRE MONDIALE DES SOCIALISMES - Elleinstein, Jean (dirección) (1984)
CONTENIDO: V.1 DES ORIGINES A 1851.-- V.2 1852-1914.-- V.3 1914-1928.-- V.4 1929-1945.-- V.5 1945-1960.--V.6 DE 1961 A NOS JOURS